MONITORING PEMAKAIAN ARUS DAN PENGENDALI INTENSITAS CAHAYA PADA LAMPU BERBASIS INTERNET OF THINGS MENGGUNAKAN ANDROID - Fatta Shofa Hasani; Choerun Asnawi; Andika Bayu Saputra; Alfun Roehatul Jannah (Jurnal Teknomatika, 2021)
The switch on and off of a light takes time when it has to be done in a lot of space. Not to mention in a multistoried building that had to turn the lights on and off on each floor of the building and in each room. Not only that, the omission in turning on and off lights would be very dangerous if left unchecked. Besides electrical waste, a fire starter will occur when lights will run continuously. To make it easier for users to engage in daily activities in turn off lights especially in many areas, it is suggested in this study that a prototype of the current monitoring system and light intensity control for lights based on the Internet of things which the design would be integrated with wi-fi and android. The prototype was built to provide the solution by turning off and turning on the lights without having to move from place to place. Designed by simple looks, the user can control it via the android. With the prototypes and created systems it is expected to make user activity easier and minimise the user negligence factor in turning on and off lights that can overload electricity to fire triggers.